Stability analysis of Automatic Voltage Regulator using Fractional Order Controller - et. al., K Muralidhar Goud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We aim to design a fractional order robust control system. It is an advanced model of classic PID controller whose order will be non-integer.PID controller that we generally use has many advantages and disadvantages with respect to the disadvantages like, it doesn’t give accurate values of constants, exact values of the time domain parameters as well as frequency domain parameters of the control system and we have more robust problem. Wearable electronic based an automatic voltage regulator can automatically preservesthe terminal voltage of generator at a fixed value under varyingly load and operating temperature. AVR controls output by sensing the output voltage at a power-generating coil and compares it to a stable reference. The combination of fractional order controller with an automatic voltage regulator is proved to be better than conventional controllers.